So near and yet so far: The specific case of Ralstonia solanacearum populations from Côte d'Ivoire in Africa - (:unkn) unknown (My University, 2012)
The genetic and phenotypic diversity of Côte d'Ivoire Ralstonia solanacearum strains was assessed on a 168-strain collection sampled on Solanaceae both in the southern lowlands and western highlands. Phylotypes I, II, and III were prevalent, though at unexpected frequencies. Phylotype I strains (87.5%) were genetically diverse and overrepresented in all agroecological areas, including highlands (AEZ III). Phylotype II strains (10.7%) only belonged to one tropical lowland-adapted broad host range lineage (IIA-35), whereas no highland-adapted potato brown rot (IIB-1) or Moko strains were detected. African phylotype III strains were rare (1.8%). They originated from a single Burkina Faso lineage (III-23) and were only found in lowlands. Three phylotype I strains were found harboring pRSC35, a plasmid identified in phylotype III strains in Cameroon. From pathogenicity tests performed on commercial varieties and tomato/eggplant/pepper references, the virulence diversity observed was high, with five pathoprofiles described. Eggplant accessions MM152 and EG203 and tomato HW7996 displayed the largest resistance spectrum and highest level. Two highly virulent phylotype I strains were able to bypass resistance of HW7996 and the eggplant reference AG91- 25. Collectively, these points lead to the conclusion that the situation in Côte d'Ivoire is specific towards other African countries, and specifically from the Cameroon reference, and that within phylotype I can exist a high virulence diversity. This calls for similar studies in neighboring West African countries, linking R. solanacearum pathogen genetic diversity to strain virulence at the regional level, for the rationalization of regional resistance deployment strategies and future resistance durability studies. (Résumé d'auteur)
Keywords: African Research